2003
DOI: 10.1128/jvi.77.19.10213-10226.2003
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Splicing Regulates Human Papillomavirus Type 11 E1 Protein Production and DNA Replication

Abstract: The papillomavirus replicative helicase E1 and the origin recognition protein E2 are required for efficient viral DNA replication. We fused the green fluorescent protein (GFP) to the human papillomavirus type 11 E1 protein either in a plasmid with the E1 coding region alone (nucleotides [nt] 832 to 2781) (pGFP-11E1) or in a plasmid containing both the E1 and E2 regions (nt 2723 to 3826) and the viral origin of replication (ori) (p11Rc). The former supported transient replication of an ori plasmid, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 80 publications
(68 reference statements)
1
36
0
Order By: Relevance
“…We have shown that a fusion protein of GFP and HPV-11 E1 (GFP-H11 E1) supports transient replication as efficiently as the wild-type E1 protein (26). However, the majority of the transcripts from a native E1 or GFP-E1 fusion expression vector contain an intragenic splice from the preferred splice donor site at nt 847 (within the sixth codon) to nt 2622 near the carboxyl terminus, just upstream of the E2 open reading frame, which overlaps the E1 coding region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that a fusion protein of GFP and HPV-11 E1 (GFP-H11 E1) supports transient replication as efficiently as the wild-type E1 protein (26). However, the majority of the transcripts from a native E1 or GFP-E1 fusion expression vector contain an intragenic splice from the preferred splice donor site at nt 847 (within the sixth codon) to nt 2622 near the carboxyl terminus, just upstream of the E2 open reading frame, which overlaps the E1 coding region.…”
Section: Resultsmentioning
confidence: 99%
“…Five micrograms of pMT2-H11 E2, 1 g of pGFP-H11 E1dm (wild type or mutation), and 0.5 g of HPV-11 ori-containing VOL. 81,2007 MAP KINASES ACTIVATE THE NLS OF HPV E1 DNA HELICASE 5067 plasmid were cotransfected into 293 cells by electroporation as described previously (26). The low-molecular-weight DNA was harvested 48 h posttransfection, using methods reported previously (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four cyclin kinase phosphorylation sites are present in E1 proteins, and mutation of these sites drastically reduces the replication activity of E1 (98). It is still not clear how E1 activity is regulated in differentiating cells, but studies with HPV-31 have shown that expression of E1 transcripts shifts from the early to late promoters, resulting in increased E1 expression (29). A shift in the absolute levels of E1 or the ratios of E1 to E2 is thought to result in high-level replication upon differentiation.…”
Section: E1 and E2 Replication Proteinsmentioning
confidence: 99%
“…Plasmid p11E1, which expresses HPV11 E1 fused at its N terminus to green fluorescent protein (GFP), was constructed by inserting an XhoI-BamHI fragment including the E1 open reading frame (ORF) between the XhoI and BamHI sites of pEGFP-C2 (Clontech). The XhoI-BamHI E1 fragment used for this construction contains the previously reported mutations inactivating the major splicing donor site (21), as well as a NotI restriction site between the stop codon of E1 and the BamHI site. The nucleotide sequence of this fragment can be summarized as follows, with the XhoI, NotI, and BamHI sites underlined and the translation initiation and termination codons of the E1 ORF in brackets and italicized: 5=-CTCGAGCCACC[ATG-E1ORF-TAG]TGAGCGGCCGCTAGTAACATATGTAGTAAGGATCC-3=.…”
Section: Methodsmentioning
confidence: 99%